Inhibiting Effects of Rabeprazole Sulfide on the Corrosion of Mild Steel in Acidic Chloride Solution - M. K. Pavithra; T. V. Venkatesha; M. K. Punith Kumar (International Journal of Electrochemistry)
The corrosion inhibition effect of Rabeprazole sulfide (RS) on mild steel in 1 M hydrochloric acid (HCl) was investigated using weight loss, potentiodynamic polarization, electrochemical impedance spectroscopy (EIS), and chronoamperometric measurements. Protection efficiency of RS increases with the concentration and decreases with the rise in temperature. Adsorption of RS on mild steel surface in 1 M HCl follows Langmuir adsorption isotherm. The kinetic and thermodynamic parameters governing the adsorption process were calculated and discussed. The polarization results suggest that RS performed as an excellent mixed-type inhibitor for mild steel corrosion in 1 M HCl.